Association between sociodemographic variables and awareness of diabetic retinopathy among type 2 diabetic patients - Muhammedali, Kasim Yasar Kannappillil; Sahasranamam, V.; Ambika, Saji Nair (International Journal of Advances in Medicine, 2020)
Background: Early detection of diabetic retinopathy (DR) is the most important factor in reducing the blinding complications due to diabetes. Study of the various socio-demographic factors affecting awareness of DR will help us to formulate effective screening programs for early detection. Objectives of the study were to find the sociodemographic determinants associated with awareness of DR and to evaluate the association of stage of DR with awareness about diabetic retinopathy. Methods: A cross sectional study was conducted among 384 patients who had been diagnosed with diabetes mellitus in various medical camps and diabetic clinics at Thiruvananthapuram. Socio demographic variables and awareness were assessed using structured self-administered questionnaire. Dilated fundus evaluation was done and retinopathy classified. Data entered to excel sheet and analysis done using statistical software (SPSS version 20). Results: Among the 384 patients, 44.9% were diagnosed to have diabetic retinopathy. Among the diagnosed 41.6% had mild non proliferative DR (NPDR), 33.0% had moderate NPDR, 11.45% had severe NPDR. 13.4% of subjects were diagnosed to have proliferative DR. 53.1% of the subjects with diabetic retinopathy had clinically significant macular edema. There was no statistically significant association between the stage of DR to awareness. Among the socio demographic variables, significant positive association with level of awareness was obtained for duration of diabetes (OR=10.96; p=0.004) Conclusions: Duration of diabetes was significantly associated with level of awareness. There was no statistically significant association between the stage of diabetic retinopathy to awareness. This signifies the urgent need to intensify our diabetic retinopathy awareness programs.